Microteaching in Isolation: Fostering Autonomy and Learner Engagement through VoiceThread - Agnes Bodis; Melissa Reed; Yulia Kharchenko (Cranmore Publishing, 2020)
As ESL and TESOL programs moved to an online or remote teaching mode rather rapidly during the first half of 2020, many of the practical elements of face-to-face teaching needed to be reconciled in the new mode. Likewise, in a TESOL teacher training unit at Macquarie University, Australia, highly practical elements of the unit needed to be changed to an online mode in line with the new restrictions. In order to address these challenges, online microteaching activities were implemented, employing the principles of Learning-Oriented Assessment (LOA) and learner autonomy. Responding to the students' needs, a series of asynchronous tasks were created using VoiceThread, a multimodal asynchronous interactive platform, and enabling tasks facilitated by a combination of videos, interactive H5P tasks and forums. We have found that the new approach not only met the Unit Learning Outcomes (ULOs), including the practical application of teaching methodologies, but also had further advantages. The additional strengths of the approach include increased feedback literacy, and information and communication technology (ICT) skills for students, developing autonomy as learners and teachers, and developing a community and fostering engagement. The present task design is applicable to English for specific purposes (ESP) and general English teaching contexts in both fully online and face-to-face delivery modes.